ETIKA LINGKUNGAN BERBASIS AL QUR’AN DAN KOSMOLOGI SUFISTIK MULLA ṢADRĀ - Kerwanto (Al Burhan: Jurnal Kajian Ilmu dan Pengembangan Budaya Al-Qur'an, 2020)
Mulla Sadra's cosmological philosophy combined with the Qur'an which is rich in spiritual values ​​can be used as a basis for building a new environmental ethic. Some of the basic principles of Mulla adrā's cosmological philosophy include: first, everything that exists, including Allah and His creation, has various hierarchies and strata of existence, which have basic and important similarities. God and His creation have an indivisible unity. Being (creation) is absolutely dependent on its Creator. Second, just as the universe with all its levels is a sign (āyah) for Allah Ta'ala, so is the Qur'an. The universe is a Big Book (Kitab Takwini), while the Qur'an is a Small Book (Kitab Tadwini). Third, as God's most perfect creation, humans have a central position and role in the hierarchy of levels of nature's existence, namely giving meaning to the reality of that existence. As the caliph of Allah, humans must do their best to maintain the balance of nature and interact fairly/correctly with other creatures (majud-majud).